Factors that contribute to professional women’s employability after Age 65 - Amandola, Debra A. (Kansas State University, 2018)
Over 76 million people between the ages of 65 and 70 years old are making the decision to continue to work or retire. The factors that contribute to professional women’s employability after age 65 who continue to work are important to understand. Many women as they approach age 65 may want to know this information as once you retire, it may be hard to turn back. Also, helping professions in gerontology and other related areas may want to encourage women to continue to work instead of just encouraging them only to retire. Work can help individuals stay healthier and mentally sharp and it takes physical health and mental sharpness to stay employed. There is a mutual benefit. An exploratory qualitative research design was selected to understand the perceptions of how professional women continue to stay employed beyond age 65. Thirteen women (N=13) were interviewed to elucidate specific factors that support delayed retirement. Since longevity and vitality are increasing, extending work life can help individuals age well. Results showed that five themes emerged after an in-depth analysis of the individual interviews, all of which greatly affect each woman’s employability after 65 years of age. These themes discovered were: (a) Enjoyment of Work, (b) Physical Health and Mental Sharpness, (c) Relationships with Work Colleagues, (d) Personal Resilience, and (e) Continuous Learning and Deep Relevant Expertise.
Keywords: Women over 65 employability; Professional women's employability; Professional women employability after age 65Women employability